COVID-19 Vaccine Perceptions and Differences by Sex, Age, and Education in 1,367 Community Adults in Ontario - Syan, Sabrina K.; Gohari, Mahmood R.; Levitt, Emily E.; Belisario, Kyla; Gillard, Jessica; DeJesus, Jane; MacKillop, James (Frontiers in Public Health, 2021)
Background: COVID-19 is a global pandemic and vaccination efforts may be impeded by vaccine hesitancy. The present study examined willingness to receive a COVID-19 vaccine, the associated reasons for willingness/unwillingness, and vaccine safety perceptions in a cross-sectional assessment of community adults in Ontario. Methods: One thousand three hundred sixty seven individuals (60.6% female, mean age = 37.5%) participated in this study between January 15, 2021 and February 15, 2021. Perceptions of vaccine safety and reasons for willingness/unwillingness to receive the COVID-19 vaccine were investigated using an online assessment. Perceptions were investigated in general and by age, sex and education using analysis of variance. Results: Overall, 82.8% of the sample reported they were willing to receive a COVID-19 vaccine and 17.2% reported they were unwilling. The three most common reasons for unwillingness were long-term side effects (65.5%), immediate side effects (60.5%), and lack of trust in the vaccine (55.2%). Vaccine willingness significantly differed by sex and education level, with female participants and those with less than a bachelor's degree being more likely to report unwillingness. Perception of COVID-19 vaccine safety was significantly lower (−10.3%) than vaccines in general and differed by age, sex and education, with females, older adults, and individuals with less than a bachelor's degree reporting lower perceived COVID-19 vaccine safety. Conclusion: In this sample of community adults, the COVID-19 vaccine hesitancy rate was less than one in five individuals, but with higher rates in population subgroups. Targeting public health messaging to females and individuals with less than bachelor's degree, and addressing concerns about long-term and immediate side effects may increase vaccine uptake.